2011
DOI: 10.1016/j.gaceta.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of skin cancer risk behaviors in Madrid (Spain)

Abstract: Numerous sociodemographic factors are related to UV radiation exposure and sunburn, with young people at highest risk. UV exposure is more frequent among women, whereas sunburn is more common among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
4
17
1
1
Order By: Relevance
“…A more prevalent use by females was observed for each participating country and was statistically significant after adjustment for important confounders such as age, education and skin type (Georgia and Turkey were exceptions due to low overall prevalence of use; Cyprus, Malta and Moldova were exceptions due to all users being females in those countries). While many studies reported that women are two‐to‐three times more likely than men to engage in indoor tanning, we found that the predominance of female users was even higher (females/males ≥3) in half of the participating countries. Interestingly, the highest disproportions (females/males ≥4) were detected in the Balkans, which we refer to as the Balkan particularity of sunbed use.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…A more prevalent use by females was observed for each participating country and was statistically significant after adjustment for important confounders such as age, education and skin type (Georgia and Turkey were exceptions due to low overall prevalence of use; Cyprus, Malta and Moldova were exceptions due to all users being females in those countries). While many studies reported that women are two‐to‐three times more likely than men to engage in indoor tanning, we found that the predominance of female users was even higher (females/males ≥3) in half of the participating countries. Interestingly, the highest disproportions (females/males ≥4) were detected in the Balkans, which we refer to as the Balkan particularity of sunbed use.…”
Section: Discussioncontrasting
confidence: 63%
“…Indeed, our multivariate analysis excluded a large effect of educational attainment on sunbed use. This might represent an indication that indoor tanning –traditionally associated with higher socio‐economic status– has started to transcend educational level and possibly social class in Europe, as previously suggested …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Indeed, this transition period in Greek Superleague takes place during June and at the beginning of July at a favorable latitude (35,9°N). During this period UVB reaches its peak [46], resulting in increased vitamin D production. It is well demonstrated the extremely importance that UVB plays on vitamin D synthesis [1], [3] and the observation that its effectiveness is among other parameters, season dependent [32].…”
Section: Discussionmentioning
confidence: 99%
“…Considering its pupolation of 47 million it represent a consumption of almost 9 million liters of sunscreen per year. According to a survey carried out in Spain, almost 80% of the population used sunscreen to protect their skin against the UV radiation (Galán et al, 2011). This percentage is significantly higher than in the United Kingdom (37%) (Miles et al, 2005) or Australia (27%) (Dobbinson et al, 2008).…”
Section: Coastal Tourism Trend and Use Of Sunscreen: The Spain Casementioning
confidence: 99%